The Dark Triad and Deception Perceptions - Wissing, Benno Gerrit; Reinhard, Marc-André (Frontiers in Psychology, 2019)
The present cross-sectional study (N = 205) tested the hypothesis that the Dark Triad traits – narcissism, Machiavellianism, and psychopathy – and the PID-5 maladaptive personality traits – Negative Affectivity, Detachment, Antagonism, Disinhibition, and Psychoticism – are associated with specific deception-related perceptions: perceived cue-based deception detectability, perceived deception production ability, and perceived deception detection ability. Participants completed personality and deception measures in an online setting. All three Dark Triad traits and Antagonism were associated with perceived deception production ability, but not (substantially) with perceived deception detection ability and cue-based deception detectability. The results provide a more fine-grained picture of biases associated with the Dark Triad traits in the context of deception and further support the relevance of Antagonism and Detachment as deception-relevant personality traits.